Digital herbarium database of some rainy season weeds of Khadar area of Hastinapur District, Meerut (U.P.), India - Shishodia, Jyoti; Saxena, R S (International Multidisciplinary Research Journal, 2012)
Digital herbarium database includes virtual images of plant specimens in digital format. This form of digital database herbarium is quite different from the traditional herbarium. In this form, the herbarium data is stored and made available to the taxonomists electronically.The modern database includes the actual herbarium specimens as digital images with all relevant informations available on the herbarium sheet label.The study of digital herbarium database reduces the time and efforts required for collection, identification and study of plants. This form of Floweringoral study reduces the cost of large herbarium maintenance. Very large information of plants can be stored in a small space. Digitization replaces the loan methods of herbarium from one institute to another for researches.Digital herbarium database is helpful in maintaining the wealth of plants. Digitized Floweringora can be represented in a compact form, this is very useful for use of forest department, ecological workers and for institutions carrying plant researches in all disciplines. The digital form of Floweringora is very useful as corrections and modifications can be made from time to time as Floweringora is never constant and undergoes changes over a period of time. The stretches of the Upper Ganges Canal is called Khadar. The present paper deals with some rainy season weeds of Khadar area of Hastinapur , district – Meerut (UP), India.